Validation of Gait Process Evaluation in People with Lower Limb Amputation - Marcin Zaczyk (Rehabilitacja Medyczna)
Objective: The gait process after lower limb amputation in a prosthesis is far from the original previously learned gait. In this paper, we present a simple method of observing and recording gait parameters. The proposed method was distinguished by the fact that gait measurement systems were permanently integrated into the prosthesis. The prosthesis became the measuring system in the study. Analysis of the parameters recorded in this way allows to unequivocally show the difference between correct gait and incorrectly realised gait in a lower limb prosthesis with high precision.Aim: The main objective of the study was to show the hallmarks of the gait process in amputees using a lower limb prosthesis (after the rehabilitation process and secondary learning of gait in a prosthesis) compared to the hallmarks of the gait process of a pre-amputee.Methods: Two people participated in the pilot study. One of them was scheduled for amputation surgery. The individual was selected using double-blind sampling from a patient base of 200 people, with Buerger's disease diagnosed at baseline. The second person underwent right lower limb amputation of the proximal third of the lower leg with a medium stump. The etiology of this amputation was Buerger's disease with necrosis of the foot with arterial congestion.Results: The results obtained in the pilot study showed that recording the loading pattern in the heel and forefoot is sufficient for unambiguous gait assessment. The obtained data allow the introduction of corrective measures in the positioning of the prosthesis, adapting it to the patient's anatomical gait style.Conclusion: The results of the study demonstrated that the analysis of foot movement can determine degree of gait correctness, and Dega's IV gait index as well as J.B. Saunders index can be the basis for evaluating gait correctness.